FINANCIAL DISTRESS: CONSUMER CYCLICALS SECTOR COMPANIES LISTED IN THE INDONESIA STOCK EXCHANGE - Indri Oktavia; Toni Nurhadianto; Ghina Fitri Ariesta Susilo (Jurnal REP (Riset Ekonomi Pembangunan), 2023)
This research aimed to prove empirically the effect of risk management disclosure and debt policy on financial distress. The data used in this research was secondary data obtained from company annual reports. The technique of the sample selection used was purposive sampling method resulting a total of 61 sample data on consumer cyclicals sector companies listed in the Indonesia Stock Exchange (IDX) for the period 2019-2021. The method used was logistic regression with SPSS version 25 as the data analysis tool. The results of this research proved that the debt policy variable has a significant positive effect on financial distress, while the risk management disclosure variable has no effect on financial distress.